Costimulation of Naive CD8(+) Lymphocytes Induces CD4 Expression and Allows Human Immunodeficiency Virus Type 1 Infection - Kitchen, Scott G. (American Society for Microbiology, 1998)
Human immunodeficiency virus type 1 (HIV-1) infection requires cell surface expression of CD4. Costimulation of CD8(+)/CD4(−) T lymphocytes by anti-CD3 and anti-CD28 antibodies or by allogeneic dendritic cells induced expression of CD4 and rendered these CD8 cells susceptible to HIV-1 infection. Naive CD45RA(+) cells responded with greater expression of CD4 than did CD45RO(+) cells. CD8(+) lymphocytes derived from fetal or newborn sources exhibited a greater tendency to express CD4, consistent with their naive states. This mechanism of infection suggests HIV-induced perturbation of the CD8 arm of the immune response and could explain the generally rapid disease progression seen in HIV-infected children.